Perspective de la grammaire générative sur l’anaphore - Philip Miller (Corela)
This paper presents the treatment of anaphora in generative grammar. After a broad review of of the different theories covered under the term, it provides an overview of the history of the treatment of anaphora in generative grammar. It then discusses Ariel’s theory of accessibility and shows how it can account for the choice of some of the anaphoric expressions provided in the text. In a final section, the paper presents the author’s recent work on the choice between verbal anaphors (Verb Phrase Ellipsis and the Verb Phrase Anaphors do it, do this, do that). It is shown that accessibility can account for some aspects of the choice but is not sufficient. Further constraints on the choice are proposed in terms of the notion of Question Under Discussion (QUD), for which experimental evidence is adduced.